Respuesta :

Answer:

A(x) = 2x² - 20x + 110

Step-by-step explanation:

A(x) = 2(x - 5)² - 60

A(x) = 2(x - 5)(x - 5) - 60

A(x) = 2[x(x - 5) - 5(x - 5)] - 60

A(x) = 2[x(x) - x(5) - 5(x) + 5(5)] - 60

A(x) = 2(x² - 5x - 5x + 25) - 60

A(x) = 2(x² - 10x + 25) - 60

A(x) = 2(x²) - 2(10x) + 2(25) - 60

A(x) = 2x² - 20x + 50 + 60

A(x) = 2x² - 20x + 110

Answer:

A(x) = 2x² - 20x - 10

Step-by-step explanation:

A(x) = 2(x - 5)² - 60 ← expand factor using FOIL

      = 2(x² - 10x + 25) - 60 ← distribute parenthesis

     = 2x² - 20x + 50 - 60 ← collect like terms

    = 2x² - 20x - 10